(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2025)
Artificial Intelligence (AI) has rapidly emerged as a transformative tool in medical diagnostics, particularly in oncology. This study explores how AI-based imaging and predictive analytics improve early cancer detection rates. Using clinical data from multiple cancer registries (2019–2023), we analyze the accuracy, sensitivity, and specificity of AI diagnostic systems compared to traditional radiological approaches. Results show significant improvement in early-stage detection for breast and lung cancers, leading to better patient outcomes and reduced mortality.